The effect of crocin on testicular tissue and sperm parameters of mice offspring from mothers exposed to atrazine during pregnancy and lactation periods: An experimental study - Masoumeh Fani; Abbas Mohammadipour; Alireza Ebrahimzadeh Bideskan (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Atrazine as a herbicide may affect the human’s health. Crocin may protect atrazine-induced damages. Objective: The aim of this study was to evaluate the effects of atrazine on mice testicular tissue and sperm parameters and protective effects of Crocin on probably atrazine-induced damages. Materials and Methods: in this experimental study, 24 pregnant Balb/c mice were randomly divided to 4 groups: I: Atrazine (10 mg/kg), II: Atrazine-Crocin, III: Crocin (10 mg/kg) and IV: Normal saline. Administrations were done daily by gavage during pregnancy and lactation. In the end, two male offspring were randomly selected from every mother and sacrificed respectively on 23 and 75 postnatal days. Then, their epididymides were removed for sperm parameters investigation and their testes were prepared to evaluate apoptosis by means of TUNEL technique. Results: The mean number of sperms in the atrazine group was lower compared to other groups and increased in the atrazine-crocin group compared with atrazine group significantly (p=0.001). Sperm abnormality was increased in the atrazine group compared with the normal saline group and decreased in the atrazine-crocin group compared with atrazine group significantly (p≤0.001). TUNEL-positive spermatogonia in 23 days old offspring increased significantly in the atrazine group compared with other groups (p=0.03). TUNEL-positive spermatogenic cells in 75 days old offspring was significantly increased in the atrazine group compared with the saline group (p≤0.001). Conclusion: Atrazine exposure may lead to decrease the number of sperms, increase sperms abnormality, spermatogenic cell apoptosis and height of germinal epithelium. These complications may improve by crocin administration.